CHRONIC ZEBRAFISH PFOS EXPOSURE ALTERS SEX RATIO AND MATERNAL RELATED EFFECTS IN F1 OFFSPRING - Wang, Mingyong (2011)
Perfluorooctanesulfonic acid (PFOS) is an organic contaminant ubiquitous in the environment, wildlife, and humans. Few studies have assessed its chronic toxicity on aquatic organisms. The present study defined the effects of long-term exposure to PFOS on zebrafish development and reproduction. Specifically, zebrafish at 8 h postfertilization (hpf) were exposed to PFOS at 0, 5, 50, and 250 μg/L for five months. Growth suppression was observed in the 250 μg/L PFOS-treated group. The sex ratio was altered, with a significant female dominance in the high-dose PFOS group. Male gonad development was also impaired in a dose-dependent manner by PFOS exposure. Although female fecundity was not impacted, the F1 embryos derived from high-dose exposed females paired with males without PFOS exposure developed severe deformity at early development stages and resulted in 100% larval mortality at 7 d postfertilization (dpf). Perfluorooctanesulfonic acid quantification in embryos indicated that decreased larval survival in F1 offspring was directly correlated to the PFOS body burden, and larval lethality was attributable to maternal transfer of PFOS to the eggs. Lower-dose parental PFOS exposure did not result in decreased F1 survival; however, the offspring displayed hyperactivity of basal swimming speed in a light-to-dark behavior assessment test. These findings demonstrate that chronic exposure to PFOS adversely impacts embryonic growth, reproduction, and subsequent offspring development. Environ.